Assessment of procoagulant potential in patients with reactive thrombocytosis and its association with platelet count. (5th January 2018) - Rottenstreich, Amihai; Shai, Ela; Kleinstern, Geffen; Spectre, Galia; Varon, David; Kalish, Yosef
Abstract: Objective: We aimed to determine hemostatic changes and characterize the procoagulant potential among patients with reactive thrombocytosis (RT). Methods: Sixty patients with RT (median platelet count 718 × 10 9 /L) and 20 healthy persons were tested for complete blood count, C‐reactive protein, von Willebrand factor (VWF), factor VIII and fibrinogen, and thrombin generation. Platelet studies, including light transmission aggregometry and Cone and Plate(let) Analyzer, were also conducted. Reticulated platelets and platelet P‐selectin expression were measured using flow cytometry. Results: Compared to patients with mild thrombocytosis (platelet count 500‐700 × 10 9 /L; n = 27), those with moderate‐to‐severe thrombocytosis (platelet count >700 × 10 9 /L; n = 33) had significantly higher fibrinogen, factor VIII, and VWF antigen and activity levels; higher endogenous thrombin potential, peak thrombin generation and velocity index levels, and shorter time‐to‐peak thrombin level. VWF antigen and activity, fibrinogen, and factor VIII were positively associated with platelet count, whereas VWF activity/antigen ratio was inversely correlated. In a multivariate analysis of RT and control participants, only platelet count predicted endogenous thrombin potential with a positive‐linear correlation. No patients developed acquired von Willebrand syndrome. Conclusions: As determined by thrombin generation, RT was associated with in vitro prothrombotic tendency, which correlated with platelet count. This may explain the increased thromboembolic risk previously reported in patients with RT.